Tapioca Crispy Crackers with Ripe Banana Peel: Snack Enrichment with Dietary Fiber and Phenolic Compounds from an Agri-Food Waste - Sirinjullapong, Aiyada; Suchaiya, Voravadee; Chokboribal, Jaroenporn (Asian Health, Science and Technology Reports, 2024)
Banana peel is rich in bioactive compounds and dietary fiber. Both tapioca starch and bananas are naturally gluten-free. As a means of waste valorization and snack enrichment, tapioca crispy crackers were enriched with banana peel, with or without flesh. The peel was from cv.Namwa bananas are in the final stages of ripening. Phenolic compounds in the ripe banana peel led to the bitterness of the enriched crackers. To increase the amount of banana peel that could be used, the peel was boiled before being incorporated into a formulation of banana peel, at 30 g /100 g of tapioca starch, and flesh at 8 g/100 g of tapioca starch, by weight. The crackers contained no preservative or synthetic coloring or flavoring agent and were assessed without further seasoning. The product was very well-received with 100% acceptance and 93.33% of the respondents were interested in buying it. More than half of the respondents regarded it as being innovative and tasty. Proximate analyses revealed that the optimized formulation contained 2.28% ± 0.08 of total dietary fiber (about 2,280% compared to 0.01% ± 0.02 of the formulation without banana) whereas no significant increase in protein content was observed. The product contained phenolic compounds at 27.26 ± 0.19 μg TAE/g. Sensory evaluation predicted that the enriched crackers, stored at 35±1 °C in a closed container, were not likely to be rejected due to any unpleasant smell of rancidity for at least 10 days. The phenolic compounds contributed by the boiled banana peel significantly suppressed the rancidification process. The optimized formulation can be used for the development of healthy antioxidant-rich, high-fiber, and high-protein snacks using high-protein food processing by-products.